2020
DOI: 10.1080/08856257.2020.1732108
|View full text |Cite
|
Sign up to set email alerts
|

Research studies on dyslexia: participant inclusion and exclusion criteria

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…This important point becomes particularly evident when the nature and characteristics of the participants involved in such studies are analyzed. Lopes, Gomes, Oliveira, and Elliott (2020) analyzed 800 studies of dyslexia, across all scientific disciplines, that had been undertaken over the past two decades and found that clear criteria for participant recruitment were rarely made explicit. In general, dyslexia was used as a catchall term to describe poor readers (and sometimes spellers) rather than a specific and clearly delineated subgroup.…”
Section: Why Is Scientific Knowledge Treated So Unscientifically?mentioning
confidence: 99%
“…This important point becomes particularly evident when the nature and characteristics of the participants involved in such studies are analyzed. Lopes, Gomes, Oliveira, and Elliott (2020) analyzed 800 studies of dyslexia, across all scientific disciplines, that had been undertaken over the past two decades and found that clear criteria for participant recruitment were rarely made explicit. In general, dyslexia was used as a catchall term to describe poor readers (and sometimes spellers) rather than a specific and clearly delineated subgroup.…”
Section: Why Is Scientific Knowledge Treated So Unscientifically?mentioning
confidence: 99%
“…It is also presumed that children with SLI or dyslexia have been given adequate learning opportunities to acquire developmentally appropriate language and reading skills (Bishop, 2006;Leonard, 2014). However, the operationalization of these exclusionary criteria is challenging and has varied over time in studies of both disorders (Lopes et al, 2020;Reilly et al, 2014).…”
Section: Defining Sli and Dyslexiamentioning
confidence: 99%
“…Still, the relations between verbal and nonverbal cognitive skills remain of interest to researchers involved in the study of language, reading, and other learning disorders (Archibald et al, 2019;Durant et al, 2019;Justice et al, 2017;Korpipä et al, 2017;Peng et al, 2019). Studies of SLI and dyslexia frequently apply nonverbal IQ cutoffs as part of their exclusionary criteria (Gallinat & Spaulding, 2014;Lopes et al, 2020). These cutoffs have been particularly important for studies aimed at understanding causal mechanisms of language or reading impairment (Leonard, 2020;Rice, 2020).…”
Section: Nonverbal Intelligencementioning
confidence: 99%
“…The cooperation between parent, child and kindergarten teacher is perhaps the most important success factor in early detection and intervention. However, as pointed out by Lopes, Gomes, Oliveira, and Elliott (2020), teachers are seldom involved, although they are the ones closest to see how the child performs and progresses and should hence be the first to observe problems. Likewise, parents are seldom involved, except as acceptors for clinical evaluation and consent authorities for their children to participate in research projects (Abd Rauf, Ismail, Balakrishnan, & Haruna, 2018).…”
Section: Finding Early Predictors Of Dyslexiamentioning
confidence: 99%
“…In all developmental research, sampling is a challenge. In longitudinal dyslexia studies, this problem has been dealt with in different ways (Lopes et al, 2020). One way has been to base samples on well-established risk groups such as clinically referred children with developmental language impairment as reported by Elbro, Dalby, and Maarbjerg (2011).…”
Section: Sample Selection and Developmental Trajectoriesmentioning
confidence: 99%